2015
DOI: 10.1097/mib.0000000000000361
|View full text |Cite
|
Sign up to set email alerts
|

Management of Intra-abdominal Abscesses in Children With Crohnʼs Disease

Abstract: Background Intra-abdominal abscesses (IAA) are complications of Crohn’s disease, which often result in hospitalization, surgery, and increased cost. Initial management may include medical therapy, percutaneous drainage (PD), or surgery, although the optimal management of IAA in children is unclear. Methods Retrospective review of all pediatric patients with Crohn’s disease who developed an IAA from January 1, 2000 to April 30, 2012. Three groups, based on initial IAA treatment modality (medical, PD, and surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…published a single centre series on young patients with intra‐abdominal abscesses with Crohn's disease. In this study, 60% of patients with intra‐abdominal abscess required surgery, and at 1 year, 67% of patients who were managed with initial non‐operative managed required surgical intervention …”
mentioning
confidence: 65%
See 1 more Smart Citation
“…published a single centre series on young patients with intra‐abdominal abscesses with Crohn's disease. In this study, 60% of patients with intra‐abdominal abscess required surgery, and at 1 year, 67% of patients who were managed with initial non‐operative managed required surgical intervention …”
mentioning
confidence: 65%
“…In this study, 60% of patients with intra-abdominal abscess required surgery, and at 1 year, 67% of patients who were managed with initial nonoperative managed required surgical intervention. 2 The literature suggests that some Crohn's disease patients with intra-abdominal abscesses may be managed non-operatively. Lee et al reported a 66.7% success rate in non-operative management of Crohn's disease patients with intra-abdominal abscess, but only without concurrent steroids and relevant fistulae.…”
mentioning
confidence: 99%
“…In addition, at the 1-year follow-up, 67% of patients who were managed with initial nonoperative management required surgical intervention [20]. When choosing conservative medical treatment, we recommend using strict indications and close clinical observation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, they would prefer US imagining over other imaging modalities for follow-up imaging (47%) [ 65 ]. Another study by Dotson et al found out that, at a single institution, CT was the imaging modality most frequently used for the follow-up imaging of Chron’s-related pediatric abdominal abscesses [ 66 ]. Such a practice differs quite significantly from that of our institution, favoring US for both initial and follow-up imaging, at least in uncomplicated cases.…”
Section: Review Of the Literaturementioning
confidence: 99%